Knowledge about Diabetes and Glycemic Control among Diabetic Patients in Saudi Arabia - Noura A. Abouammoh; Muteb A. Alshamrani (Journal of Diabetes Research)
The prevalence of diabetes in various regions has attracted significant attention of the medical experts. The prevalence of diabetes is expected to increase in the future due to changes in lifestyle and unhealthy diets of individuals. The objective of the study is to identify the extent of knowledge related to diabetes and glycemic controls in various diabetic patients living in Saudi Arabia. A total of 435 patients were recruited using a random sampling technique, while following a cross-sectional design. Patients’ knowledge was tested using the Michigan Diabetes Knowledge Test. Findings of the study illustrated that the problem was common among middle-aged male patients. A significant amount of knowledge related to the consumption of medicines, insulin, healthy diet, etc. was found among diabetic patients. Despite the fact that people have adequate knowledge, valuable attention is yet required to provide necessary counselling to people living in Saudi Arabia that may help them to control health risks and mortality.